PERAN ADVOKAT DALAM PENDAMPINGAN KLIEN PADA PERKARA PERCERAIAN PERSPEKTIF HUKUM POSITIF - Siti Maimuna (Sekolah Tinggi Agama Islam Miftahul Ulum Lumajang, 2023)
The role of the advokat in assisting clients in divorce cases still raises many pros and cons in society. This causes the good name of the profession to be tarnished, therefore with the existence of an advokat law and an advokat code of ethics, the profession can maintain the good name of the profession. The existence of these arguments led to a loss of enthusiasm from legal scholars to become advokats. This research examines how positive legal views are on the role of advokats in assisting clients in divorce cases which still cause many incompatibilities with existing legal rules. This research is a qualitative research using a normative approach. The results of this research indicate that an advokat in assisting his client must comply with the advokat law and the advokat's code of ethics and if the advokat violates the legal umbrella, legal action will still apply. In the view of positive law, namely referring to written law according to the provisions of the law.